2021
DOI: 10.1016/j.scitotenv.2021.146040
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and on-site simulation of environmental transmission of SARS-CoV-2 in the largest wholesale market of Beijing, China

Abstract: From June 11, 2020, a surge in new cases of coronavirus disease 2019 (COVID-19) in the largest wholesale market of Beijing, the Xinfadi Market, leading to a second wave of COVID-19 in Beijing, China. Understanding the transmission modes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the personal behaviors and environmental factors contributing to viral transmission is of utmost important to curb COVID-19 rise. However, currently these are largely unknown in food markets. To this end, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…2 A subsequent study using field investigations and onsite simulations at Xinfadi market suggested the virus could spread from contaminated goods to humans, and environmental factors such as low temperature and high humidity, poor ventilation, and insufficient hygiene facilities and disinfection practices might contribute to viral transmission. 3 A further cluster of cases was reported in July 2020 in Dalian, China, the first of which was in an employee of a cold chain food company. 4 No local infections had been reported in Dalian for 111 consecutive days before this case was confirmed.…”
Section: Reported Casesmentioning
confidence: 97%
“…2 A subsequent study using field investigations and onsite simulations at Xinfadi market suggested the virus could spread from contaminated goods to humans, and environmental factors such as low temperature and high humidity, poor ventilation, and insufficient hygiene facilities and disinfection practices might contribute to viral transmission. 3 A further cluster of cases was reported in July 2020 in Dalian, China, the first of which was in an employee of a cold chain food company. 4 No local infections had been reported in Dalian for 111 consecutive days before this case was confirmed.…”
Section: Reported Casesmentioning
confidence: 97%
“…People working in the cold chain or receiving deliveries are at risk of infection. A previous study suggested that poor ventilation and insufficient hygiene facilities may increase the risks of infectious disease outbreaks ( 6 ). Supermarkets, shopping malls, restaurants, and other public places have a large flow of people, but code scanning and body temperature measurement under normal epidemic prevention and control conditions are not carefully implemented.…”
Section: Risks During Normal Epidemic Conditionsmentioning
confidence: 99%
“…In addition, when people walked around, they will influence the airflow and spread fluorescent microspheres to other places. It has also been confirmed that human activities can affect bacteriacarrying particles in a study (8). After simulating breathing and coughing or sneezing of infected persons, fluorescent microspheres can persist in the air and the particle sizes were mainly between 0.3 μm and 0.5 μm.…”
Section: Discussionmentioning
confidence: 57%
“…Some fluorescent microspheres can settle to the surface of tables, windowsills, and other objects after coagulation. Presently, the research on SARS-CoV-2 transmission usually focused on the simulation cabin experiment or computational fluid dynamic model ( 9 - 10 ). This result provided a basis for epidemic prevention and control and experimental support for future research.…”
Section: Discussionmentioning
confidence: 99%